GAMBARAN KINERJA RUMAH SAKIT SEBELUM DAN SESUDAH ERA JAMINAN KESEHATAN NASIONAL (JKN) - Wiwik Lestari; Laksono Trisnantoro; Ni Luh Putu Eka Putri Andayani (Journal of Health Service Management, 2021)
Background: Changes in the Hospital (RS) business environment have occurred significantly since JKN was introduced by BPJS Kesehatan. In this era, hospital managers are confused about the following changes and hospital performance is declining. Objective: This study measures the service and financial performance before and after the JKN era. Methods: Descriptive research design with quantitative methods at RSKIA SADEWA. The data used are secondary data from medical record data, hospital service data and financial statements (2011-2019) Results: After the implementation of the JKN program, there was an increase in the number of patient visits by 35.23% for outpatients and 36.43% for inpatients. The percentage of inpatients who used health insurance before the JKN era was only around 3%, and after the JKN era the number increased sharply to 73%. BOR increased by 1.83%. The SC rate decreased by 0.83%. Of all general patients with Caesarean Sectio in RSKIA SADEWA, an average of 54.75% were BPJS participants, but aborted their BPJS rights. The average hospital revenue increased by 93.72%, operating costs decreased 5.78%, HR costs increased 1.52% and net profit increased 4.26%. The proportion of hospital revenue obtained from BPJS patients on average is 26.38% of the total hospital revenue. The average ROA after JKN era increased 5,96%. The average financial quick ratio increased by 443%. The average financial solvency decreased by 0.03. The average CRR increased by 7%. Conclusion: After the JKN era, there was an increase in the number of outpatient and inpatient visits. BOR increases, and SC rate decreases. Financial performance is measured by indicators of ROA, Quick Ratio, solvency and CRR. All indicators show an improvement, and there is no change in the environment after implementing the JKN program. Strict evaluation is needed to maintain and improve the achieved performance.